KEARIFAN LOKAL: BUDAYA TAHLILAN LINTAS KEYAKINAN DI CIREBON - Sarip Sarip (Jurnal An-Nufus, 2021)
Apart from the pros and cons of tahlilan among Muslims, there are those who do Tahlilan, some are not. For those who do not carry it out in a postulate it is not Islamic teachings originating from the Qur'an and Hadith. Some argue Tahilan is a party that only costs money. The events carried out by various religions and beliefs in the Capar II Block especially the Mosque Block, Urug Block, Sipedang Block, Silawet are a form of religious pluralism. Understanding of Tahlilan in Blok Capar II Hamlet is a real and inseparable part of community life. Integrating tradition or local wisdom values ??with religious values ??is a characteristic of the community of Blok Capar II Hamlet. Tahlilan, which was attended by various religious followers, is a form of religious pluralism that is still difficult to find. Religious pluralism, forming the law of society which later confirmed studies of religious pluralism.